Presenting Symptoms Independently Predict Mortality in Septic Shock: Importance of a Previously Unmeasured Confounder*. Issue 10 (October 2018) - Filbin, Michael R.; Lynch, James; Gillingham, Trent D.; Thorsen, Jill E.; Pasakarnis, Corey L.; Nepal, Saurav; Matsushima, Minoru; Rhee, Chanu; Heldt, Thomas; Reisner, Andrew T.
Abstract : Objectives: Presenting symptoms in patients with sepsis may influence rapidity of diagnosis, time-to-antibiotics, and outcome. We tested the hypothesis that vague presenting symptoms are associated with delayed antibiotics and increased mortality. We further characterized individual presenting symptoms and their association with mortality. Design: Retrospective cohort study. Setting: Emergency department of large, urban, academic U.S. hospital. Patients: All adult patients with septic shock treated in the emergency department between April 2014 and March 2016. Interventions: None. Measurements and Main Results: Of 654 septic shock cases, 245 (37%) presented with vague symptoms. Time-to-antibiotics from first hypotension or elevated lactate was significantly longer for those with vague symptoms versus those with explicit symptoms of infection (1.6 vs 0.8 hr; p < 0.01), and in-hospital mortality was also substantially higher (34% vs 16%; p < 0.01). Patients with vague symptoms were older and sicker as evidenced by triage hypotension, Sequential Organ Failure Assessment score, initial serum lactate, and need for intubation. In multivariate analysis, vague symptoms were independently associated with mortality (adjusted odds ratio, 2.12; 95% CI, 1.32–3.40; p < 0.01), whereas time-to-antibiotics was not associated with mortality (adjusted odds ratio, 1.01; 95% CI, 0.94–1.08; p = 0.78). Of individual symptoms, only the absence of fever, chills, or rigors (odds ratio, 2.70; 95% CI, 1.63–4.47; p < 0.01) and presence of shortness of breath (odds ratio, 1.97; 95% CI, 1.23–3.15; p < 0.01) were independently associated with mortality. Conclusions: More than one third of patients with septic shock presented to the emergency department with vague symptoms that were not specific to infection. These patients had delayed antibiotic administration and higher risk of mortality even after controlling for demographics, illness acuity, and time-to-antibiotics in multivariate analysis. These findings suggest that the nature of presenting symptoms is an important component of sepsis clinical phenotyping and may be an important confounder in sepsis epidemiologic studies. Abstract : Supplemental Digital Content is available in the text.